Improving Learning Achievement in Elementary Schools through an Active Learning Approach - Bungati, Lisa (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study delves into the use of dynamic learning methods in elementary schools, with a focus on teachers' viewpoints, experiences, and obstacles. By conducting semi-structured interviews with 15 college instructors, a range of valuable insights were gathered regarding the implementation and effectiveness of active learning teaching methods. Thematic analysis unveiled the significance of promoting scholar engagement, collaboration, and critical inquiry to improve learning outcomes and nurture 21st-century skills. Despite the transformative potential of dynamic learning, challenges such as institutional constraints and pressures from standardized testing hinder widespread acceptance.